2019
DOI: 10.1007/s11130-019-00767-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Substances in Wheat Malt Inducing Antisecretory Factor

Abstract: Extensively malted cereals counteract enterotoxic diarrhea and inflammatory bowel diseases. This effect depends on a protein called antisecretory factor (AF), which is secreted into the blood as a larger complex known as the compleasome. In this study, we identified anti-inflammatory substances in malt and assayed their capacity to induce AF. Guaiacol and quercetin inhibited inflammation in a mouse footpad model, while catechin, sinapic acid, ferulic acid, and quercetin inhibited nitric oxide formation in RAW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For most of the currently available therapeutic options, significant limitations remain, which raises a major concern for identifying novel therapeutic options [34]. Quercetin exerts anti-inflammatory activity in multiple different disease models [35][36][37]. Hu et al [4] found that quercetin alleviated OA by attenuating the inflammation and apoptosis of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For most of the currently available therapeutic options, significant limitations remain, which raises a major concern for identifying novel therapeutic options [34]. Quercetin exerts anti-inflammatory activity in multiple different disease models [35][36][37]. Hu et al [4] found that quercetin alleviated OA by attenuating the inflammation and apoptosis of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin exerts an obvious anti-inflammatory activity in many animal species, [25][26][27] and SAA as an inflammatory marker was reduced significantly in the obesity disease cats as well as in the healthy controls. MDA concentrations were not changed in the obesity disease cats, and this phenomenon may indicate insufficiency of anti-oxidant activity of quercetin derivative.…”
Section: Discussionmentioning
confidence: 95%
“…29 Quercetin has been demonstrated to exert anti-inflammatory activity in multiple disease models. [30][31][32] However, the anti-inflammatory activity of quercetin during OA development and progression is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to find new therapeutic agents to mitigate the development and progression of OA in vulnerable patients 29 . Quercetin has been demonstrated to exert anti‐inflammatory activity in multiple disease models 30–32 . However, the anti‐inflammatory activity of quercetin during OA development and progression is not fully understood.…”
Section: Discussionmentioning
confidence: 99%